Rainfall as a trigger of ecological cascade effects in an Australian groundwater ecosystem - Mattia Saccò (Nature Portfolio, 2021)
Abstract Groundwaters host vital resources playing a key role in the near future. Subterranean fauna and microbes are crucial in regulating organic cycles in environments characterized by low energy and scarce carbon availability. However, our knowledge about the functioning of groundwater ecosystems is limited, despite being increasingly exposed to anthropic impacts and climate change-related processes. In this work we apply novel biochemical and genetic techniques to investigate the ecological dynamics of an Australian calcrete under two contrasting rainfall periods (LR—low rainfall and HR—high rainfall). Our results indicate that the microbial gut community of copepods and amphipods experienced a shift in taxonomic diversity and predicted organic functional metabolic pathways during HR. The HR regime triggered a cascade effect driven by microbes (OM processors) and exploited by copepods and amphipods (primary and secondary consumers), which was finally transferred to the aquatic beetles (top predators). Our findings highlight that rainfall triggers ecological shifts towards more deterministic dynamics, revealing a complex web of interactions in seemingly simple environmental settings. Here we show how a combined isotopic-molecular approach can untangle the mechanisms shaping a calcrete community. This design will help manage and preserve one of the most vital but underrated ecosystems worldwide.